Pengaruh Model Pembelajaran Inkuiri Oleh Guru PAK Terhadap Kreativitas Belajar Siswa Kelas VII SMP Negeri 5 Sipahutar Kabupaten Tapanuli Utara Tahun Pembelajaran 2022/2023 - Anjelina Pardede; Dame Taruli Simamora; Sandy Ariawan; Rida Gultom; Ronny Simatupang (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The aim of this research is to find out whether there is a positive and significant influence of the inquiry learning model on the learning creativity of class VII students at SMP Negeri 5 Sipahutar, Sipahutar District, North Tapanuli Regency for the 2022/2023 Academic Year. The research method used is an inferential descriptive quantitative research method. The population is all class VII students at SMP Negeri 5 Sipahutar, Sipahutar District, North Tapanuli Regency for the 2022/2023 academic year, totaling 102 people and a sample of 46 people was determined using random sampling techniques. Data was collected using a closed questionnaire with 35 items, namely 18 items for variable X and 17 items for variable Y and was tested on 36 students who were not research respondents. The results of data analysis show that there is a positive and significant influence of the inquiry learning model on the learning creativity of class VII students at SMP Negeri 5 Sipahutar, Sipahutar District, North Tapanuli Regency for the 2022/2023 Academic Year: 1) Test the analysis requirements: a) test a positive relationship to obtain an rxy value = 0.664 > rtable(a=0.05,n-2=46-2=44) = 0.2907. b) Testing a significant relationship obtained tcount= 5.883 > ttable(a=0.05, dk=n-2=44)= 2.021. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂="13.32"+0.66X. b) Regression coefficient of determination test (r2) = 44%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=25, dk denominator=n-2=46-2=44) namely 34.60 > 1.51. Thus Ha is accepted and H0 is rejected.